Short-Term Efficacy and Safety of Oral and Nasal Corticosteroids in COVID-19 Patients with Olfactory Dysfunction: A European Multicenter Study - Sven Saussez; Luigi Angelo Vaira; Carlos M. Chiesa-Estomba; Serge Daniel Le Bon; Mihaela Horoi; Giovanna Deiana; Marzia Petrocelli; Philippe Boelpaep; Giovanni Salzano; Mohamad Khalife; Stephane Hans; Giacomo De Riu; et al. (Pathogens, 2021)
Background: The objective of this study was to investigate the efficacy and safety of early administration of oral corticosteroids (OC) or nasal corticosteroids (NC) as an add-on to olfactory training (OT) versus OT alone in patients with olfactory dysfunction (OD) related to coronavirus disease 2019 (COVID-19). Methods: Patients with a positive diagnosis of COVID-19 and OD were prospectively recruited from March 22 to December 15, 2020 from 4 European hospitals. Patients had confirmed OD on psychophysical testing. All patients undertook OT, with add-on 10 days of OC (group 1: OC + OT), or 1 month of NC (group 2: NC + OT) or olfactory training alone (group 3: OT). Olfactory evaluations (Sniffin’Sticks tests) were carried out at the time of inclusion, 1 and 2 months after the start of the therapeutic course. Results: A total of 152 hyposmic or anosmic patients completed the study. Group 1, 2 and 3 included 59, 22 and 71 patients, respectively and all patient groups were comparable regarding baseline Sniffin’Sticks tests. The median Sniffin’Sticks test values significantly improved from pre- to post-intervention in all groups. The increase of Sniffin’Sticks test values was higher in group 1 (OC + OT) compared with groups 2 and 3 (p < 0.001) at one month after treatment but did not remain so at 2 months. Groups 1, 2 and 3, respectively, presented parosmia in 20/71 (28.2%), 9/22 (40.9%) and 42/71 (59.2%) patients. This difference was statistically significant between group 1 and 3 (p < 0.001). There were no patients with a worsening of the disease or an increase of the severity of the COVID-19 symptoms. Conclusions: The use of OCs in patients with OD related to mild COVID-19 is generally well-tolerated without any case of deterioration of symptoms. OC is associated with greater improvement in psychophysical olfactory evaluations at 1-month post-treatment but there was no difference at 2 months. Parosmia may be reduced following treatment with OC and NC. On the basis of these preliminary results, it is possible to state that considering the 2 months efficacy of OC and NC with respect to the OT alone and the risk-benefit ratio, the benefit to start a specific treatment of COVID-19 related OD cannot be demonstrated and there is a need for a randomised controlled trial to assess this further.